The Long-Term Impact of Work and Education on Compliance of APD Uses on Hospital Road Care Employees - Budi Kusumawardhani, Oktavy; Karsidi, Ravik (LPPM Universitas Duta Bangsa Surakarta, 2024)
The length of employment and the level of employee education significantly affect how employees carry out their tasks, particularly the use of self-protection devices (APD) in hospitals. APD usage is essential for reducing risks, especially for road care workers who face high infection risks due to the daily turnover and delayed treatment of patients. Unlike general hospital patients who stay for an average of two to five days, road care workers encounter new patients constantly, increasing their infection risk. This study aims to examine the impact of employment length and education level on APD compliance among RSUD road care employees in Karanganyar district. Using quantitative methods, the research was conducted at RSUD Karanganyar, involving 64 road care workers selected through stratified and random sampling. Data were collected via questionnaires and analyzed using double linear regression. The results indicated that both employment length and education level significantly influence APD compliance among RSUD road care workers, with a significance value of 0.049 < 0.05. In conclusion, both work duration and educational background play a crucial role in ensuring APD compliance among these workers.